(untitled) (ENTRENOVA - ENTerprise REsearch InNOVAtion, 2015)
Corruption in the public sector is problem that almost all countries in the world face with, in greater or lesser extent. During couple of past years, Bosnia and Herzegovina has had a constant growth of corruption. According to the Corruption Perception Index, Bosnia and Herzegovina has moved from 72nd position in 2013 to 80th position in 2014, with scores that had led it nearly to zones with high levels of corruption. Due to the fact that corruption in the public sector discourages innovation and entrepreneurship, and thus leaves extremely harmful effects on the entire economy of the country, at the end of 2013 research was conducted on a sample of 208 public officials and experts in the fields of accounting and auditing. The objective of the research was to determine the extent to which specific accounting tools can contribute to the suppression, or at least reducing, corruption in the public sector of Bosnia and Herzegovina. Research results showed that implementation of the program budgeting and responsibility accounting, through the efficient allocation of scarce budgetary resources between programs and the establishment of public accountability, can help the fight against corruption, improve the business climate and innovations, and thus contribute to the development of the whole country. This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.